Mengembangkan kontrol diri anak dengan teknik token ekonomi - Aziz, Al Fira Elisa (Maliki Interdisciplinary Journal, 2024)
Self-control is an important ability in a child's daily life. With self-control, children can process the emotions they feel, are able to solve problems they are facing, and collaborate with others. Children who have good self-control will be able to channel and deal with the right emotions. Meanwhile, children who have low self-control will have difficulty building relationships with other people and have difficulty adapting. Therefore it is necessary to develop self-control abilities in children. The background of the authors who found that there has been no study regarding the development of children's self-control using the token economy method has not been discussed specifically. The result is that the token economy method can be very effective if the planning and targets are reasonable and realistic. Some of the importance of self-control in children and the stages of the token economy will be explained further in this paper.